Compound Xuanju capsules combined with phosphodiesterase-5 inhibitors as a new strategy for erectile dysfunction: a meta-analysis and trial sequential analysis - Ronghui Li; Min Liao; Yunfeng Yu; Bing Guo; Rong Yu; Qinghu He; Qinghu He; Guomin Zhang (Frontiers in Pharmacology, 2025)
ObjectiveThe efficacy of compound Xuanju capsule (CXC) in the treatment of erectile dysfunction (ED) remains unclear. This study aimed to quantitatively assess the benefits and risks of CXC in the treatment of ED.MethodsEight major databases were systematically searched for relevant literature published till 10 May 2025. Studies were screened based on established criteria; meta-analysis and trial sequential analysis of included literature were conducted.ResultsThe meta-analysis demonstrated that, compared with phosphodiesterase type 5 inhibitors alone, the combination of CXC and phosphodiesterase type 5 inhibitors significantly improved the International Index of Erectile Function (IIEF)-5 score by 3.19 points (mean difference [MD] = 3.19; 95% confidence interval [CI]: 2.42–3.96; P < 0.00001), clinical effectiveness rate by 23% (risk ratio [RR] = 1.23; 95% CI: 1.15–1.32; P < 0.00001), penile cavernous blood flow by 5.21 cm/s (MD = 5.21; 95% CI: 4.43–6.00; P < 0.00001), and serum testosterone levels by 4.09 nmol/L (MD = 4.09; 95% CI: 3.14–5.04; P < 0.00001). There was no significant difference in total adverse events between the groups (RR = 0.94; 95% CI: 0.62–1.42; P = 0.77). Trial sequential analysis confirmed that the meta-analysis results for IIEF-5, clinical effectiveness rate, penile cavernous blood flow, and serum testosterone levels were conclusive. However, the results of adverse events require further validation through additional similar studies. Funnel plot analysis and Egger’s test indicated no potential publication bias for outcomes other than the clinical effectiveness rate.ConclusionCXC improves erectile function and testosterone levels in patients with ED without increasing the incidence of adverse events. These findings support the potential role of CXC as an adjunctive treatment for ED. However, due to the limitations in the quality of the current evidence, further validation through multicenter, randomized, double-blind controlled trials is necessary.